Sosiologi Hukum : Mitigasi Dampak Global Warming Sebagai Role Model Konservasi Sumber Daya Alam di Tambling Wildlife Nature Conservation (TWNC) - Arief Fahmi Lubis (Jurnal Pengabdian Masyarakat Waradin, 2022)
Habitat shifts and species distribution occur in response to climate change, while coral reefs face threats from warming oceans. These threats require effective conservation adaptation efforts, considering pollution risks, ecosystem health, and water resource sustainability. The purpose of this study is to show that currently Indonesia is facing significant challenges related to the destruction of natural resources and the environment. High deforestation, caused by illegal logging activities and the expansion of oil palm plantations, is a major cause of habitat loss and threats to biodiversity. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description when the research is carried out. The results of this study show that increasing the active participation of all components of the nation to achieve forest management goals, increasing the implementation of the Eco Tourism program as a mitigation effort in overcoming pollution risks, ecosystem health, and sustainable water resources to mitigate the impact of global warming in the context of National Resilience.